Assessment of the Nasal Bone by 2-Dimensional Ultrasound in 2 Different Planes: Do They Give the Same Results? - Kavak, Salih Burcin; Kavak, Ebru Celik (Wiley, 2020)
Objectives Measurement of the nasal bone is an important part of the genetic sonogram. This study aimed to compare nasal bone length measurements taken in 2 different planes and to determine whether there is consistency between the measurements. Methods The nasal bone was measured in 103 fetuses whose mothers were admitted to our clinic for second-trimester ultrasound examinations and who did not have any accompanying diseases. In this prospective study, the gestational ages of fetuses ranged from 19 to 23 weeks. Nasal bones were measured in both coronal and midsagittal planes, and the similarity between the measurements was evaluated. Pearson correlation, Wilcoxon signed rank, and Kruskal-Wallis tests were used to evaluate the results. Results The median nasal bone length increased with increasing gestational age in both planes, as expected. There were no statistically significant differences between the fetal nasal bone lengths taken in the midsagittal and coronal planes at 19 to 23 weeks' gestation (P > .05). Conclusions The coronal plane may be used as an alternative to evaluate the nasal bone in the second trimester of pregnancy.
Keywords: coronal plane; fetal nasal bone length; midsagittal plane; 2-dimensional ultrasound